In vitro evaluation of the antioxidant, cytotoxic, and wound healing activities of natural source extracts (Revista Brasileira Multidisciplinar, 2026)
Due the increasing concern for sustainable lifestyle, products of natural origin are gaining greater prominence in the market. Cosmetics based on plant derivatives are referred to as phytocosmetics and, to enable their use, it is necessary to guarantee their safety and efficacy. In this regard, the present study evaluated the antioxidant, cytotoxic and the wound healing in vitro activities of Stryphnodendron adstringens, Centella asiatica and HYPSKIN® extracts. The Total Phenolic Compounds Content quantification was performed using the Folin-Ciocalteu methodology and the antioxidant activity was determined with DPPHº and ABTSº+ radicals. The cell lines HDFa, HaCat and HepG2 were used for cytotoxicity assay (MTT), whereas HDFa and HaCat cell lines were applied in the wound healing assay. The HYPSKIN® extract, at the concentrations tested, doesn’t contain phenolic compounds and didn’t show antioxidant activity. The S. adstringens extract contains 44.23±0.68 μg of CFEAG/100 μg, presenting an EC50 of 3.93 μg/mL for DPPHº and 1.88 μg/mL equivalent to 1000 μM of Trolox for ABTSº+. The IC50 for HaCat, HDFa and HepG2 were 0.1036±0.0312 mg/mL, 0.1974±0.0439 mg/mL and 0.1084±0.006 mg/mL, respectively. The C. asiatica extract contains 4.36±0.42 μg of CFEAG/100 μg of extract, with EC50 of 61.82 μg/mL for DPPHº and 38.1 μg/mL equivalent to 1000 μM of Trolox for ABTSº+. The IC50 for HaCat, HDFa and HepG2 were 0.5590±0.1043 mg/mL, 0.4797±0.0367 mg/mL and 0.4675±0.0677 mg/ml, respectively. The three extracts demonstrated healing activity in HDFa cell line.
Keywords: antioxidant; cytotoxicity; wound healing; in vitro; natural extracts